Unpacking the Constituents of Dynamic Capabilities: A Microfoundations Perspective - Versailles, David; Foss, Nicolai (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2019)
This position paper updates about methodological and epistemological issues on the micro-foundations perspective. We propose that conceptual divergences between the different streams of contributions to dynamic capabilities (DCs) research (the Eisenhardt versus Teece divide) hide discrepancies about methodological aspects, and about the locus of DCs. We zoom out from current epistemological debates about the microfoundations to explain the necessity of multi-level approaches, and to clarify the interpretation of the Boudon-Coleman “bathtub”. We elaborate on these aspects to explain how to enhance research on DCs, and more generally in strategic management. We discuss specific issues in relation with the selection of units of analysis and with the elaboration of field research protocols. We also propose practical recommendations adhering to the micro-foundations approach.